ELEMENTARY SCHOOL LITERACY EDUCATION GAME APP TO INCREASE READING INTEREST - Leni Marlina; Sri Wahyuni; Febry Nurandika (Journal of Information Technology, computer science and Electrical Engineering, 2025)
This research developed an Android-based literacy education game application aimed at elementary school students. With the increasing need for good literacy skills among children, this app is designed to make the process of learning to read and write more interesting and interactive.The app includes a variety of features, such as word games, puzzles, and quizzes designed to improve reading skills and understand text. Each game is designed with a pedagogical approach that is in accordance with the elementary school curriculum, so that it can support learning in the classroom. The trial was carried out in several elementary schools involving 100 students. The results of the evaluation showed that the use of this application increased students' interest and motivation in learning literacy. The average literacy skill score of students increased by 30% after using the app for 4 weeks. From this study, it is concluded that Android-based literacy education game applications are effective in improving the literacy skills of elementary school students. Recommendations for further development include adding content and interactive features to expand the student learning experience.